Key to species of the leafhopper genus Membranacea Qin & Zhang (Hemiptera, Cicadellidae, Typhlocybinae, Empoascini), with a new species from China - Yu, Xiaofei; Yang, Maofa (Zootaxa, 2014)
A new species Membranacea distincta sp. nov. is described and illustrated from China. A key, based on the male genitalia, is given to separate all six species of the genus. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).